Futures, intimacies, animisms: Unfinished anthropologies in the twenty-first century. Issue 1 (3rd April 2018) - Collins, Samuel Gerald
Abstract: This essay explores recent work in future-oriented anthropology that develops emancipatory, anticipatory, multi-modal, and participatory approaches. Through critiquing hegemonic assumptions in anthropology and in Western modernity, these works evoke both present complexity and future potentiality. Ultimately, the essay explores these works as redemptive strategies for an anthropology besieged by intolerance and authoritarianism while grappling with its colonialist underpinnings.